PENGARUH PENERAPAN SKEMA INSENTIF BERBASIS TOURNAMENT DAN QUOTA TERHADAP KINERJA INDIVIDU DENGAN FAKTOR TASK ATTRACTIVENESS SEBAGAI VARIABEL MODERASI - Ludji, Theodorus Radja; Murniati, Monika Palupi (Jurnal Akuntansi Bisnis, 2014)
This study reports the comprehensive result of a laboratory experiment where subjects performed a problem-solving task under two types of incentive schemes; tournament and quota. Additionally, all subjects evaluated attractiveness of the task that they are perceived prior to learning how they would be compensated during the experiment. Data are collected through 2 x 2 between-subject experiment which treatment are given to incentive schemes and task attractiveness variables. Data of this experiment were analyzed with various statistical instruments such as T-Test and ANOVA. The result shown a difference in between-subject average individual performance for each incentive scheme applied in this experiment regarding of task attractiveness factor, thus proved that task attractiveness factor has causing main effect to individual performance. Furthermore, it is shown that when the task was initially perceived as being attractive, subjects under tournament incentive scheme will outperform subjects under quota incentive scheme. Conversely, when the task was initially perceived as being unattractive, subjects under quota incentive scheme will outperform subjects under tournament incentive scheme in terms of individual performance. Keywords: individual